World wheat and barley outlook - White B. (Feed manufacturing in Southern Europe: New challenges, 1997)
The author begins describing the 1995-96 period in the world and the forecast for the 1996-97 period for barley and wheat. He explains the functions of the Canadian Wheat Board and the changes introduced in the production system in Canada. He also describes the activities of the United States and Canada in the world market of wheat, firstly, and barley, secondly, specially mentioning the exportations of these countries. Finally, he predicts the situation of the world market for the 1996-97 period.
South European Feed Manufacturers Conference, 1996/05/09-11, Reus (Spain)